The role of using value-oriented management in the scope of construction projects - Nakhimi Mokhammad Yasin Mokhammad Khusain (КНУБА, 2019)
This paper describes the creation and methods of using a value-oriented approach in managing the scope of construction projects. In the framework of this approach, the following tasks are solved: the project’s value management functions are determined, project value identification is underway, values of all project stakeholders are determined, structure of value is formed in the process of managing construction projects, principles of value creation are proposed at each stage of the construction project. Implementation of this methodology will help the decision makers to better understand their goals in the project and turn them into functional solutions. The article uses the following methods: P2M standard value approach, engineering values, value management. The processes (steps) of engineering value management were described in detail, as well as the method of "Five "E" and “Two "A" (the value approach of the standard P2M). The advantages of using the value approach as the basis for managing the scope of construction projects are characterized.
Keywords: value; value creation; value management; value-oriented management; value engineering; stakeholders; construction project; 005.8; 69.003:005.591.6